Mapping the transition from a traditional university into an entrepreneurial university - Naidoo, Tharusha (Rhodes University, Faculty of Commerce, Rhodes Business School, 2021)
The study aims to map the transition of a traditional university into an entrepreneurial university. The concept of the entrepreneurial university has been established as a game changer in the development and innovation spheres at higher education institutions worldwide. In the year 2002, the South African Higher Education sector embarked on a modelling and redefining journey which gave birth to the National Plan for Higher Education. The Entrepreneurship Development in Higher Education has undertaken work done on the entrepreneurial university which gave rise to the mapping that breeds ground towards policy. This study sought to investigate whether there is a conducive environment at Rhodes University, with an entrepreneurial climate to develop institutional capabilities and build new networks. The research highlights the current direction of Rhodes University and elaborates on the potential for the transition towards an entrepreneurial university. An overview of the entrepreneurial university was provided through an analysis of literature, which dominated in the more developed countries compared to South Africa. The researcher adopted a qualitative research study to capture the direct experiences of the individuals that are in the institution. A questionnaire was designed using the Organisation for Economic Co-operation and Development Guiding Framework and the direct perceptions of academics from the university were documented. The objectives were firstly, to explore elements of leadership and governance that enhance transformation of Higher Education Institution from a traditional university towards an entrepreneurial university. Secondly, to investigate internal resources that enhance Organisational Capacity with specific reference to people and incentives. Lastly, to determine how Teaching and Learning strengthen entrepreneurship development. The interviews revealed that the challenges faced by the institution were closely linked to those recognized by existing literature. What was interesting to note, limited funding and support were regarded as the most significant problems, closely followed by unskilled people and lack of infrastructure. It is suggested that cultivating and nurturing an entrepreneurial culture is of paramount importance together with the creation of a policy framework. Furthermore, the study concluded with practical recommendations proposed to management regarding the three strategic lenses. The research also illustrated that Rhodes University may not be viewed as being entrepreneurial but certainly has pockets of entrepreneurship and innovative activities.
Keywords: Rhodes University -- Management; Education, Higher -- South Africa; Education, Higher -- Economic aspects -- South Africa; Academic-industrial cooperation; Entrepreneurship; Business and education -- South Africa; Research -- Economic aspects -- South Africa -- Case studies